A Mental Health App Adoption: Perception, Social Dynamics and Mental Health Need Moderation - Kartini, I Gusti Ayu Intan; Darma, Gede Sri; Sutrisna, I Putu Belly (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to look at the factors that influence people's intention to use mental health app selfcare.id with an emphasis on perceived ease of use, perceived usefulness, social influence, trust, and stigma in digital mental health service, and how mental health needs can moderate the impact of these variables. The research technique used is explanatory research, with 100 sample data collected through questionnaires sent to selfcare.id users and analyzed using the PLS-SEM method. The research findings reveal the indirect effects of social influence, trust, and stigma on intention to use the selfcare.id application through mental health needs are not mediated, but the effect of mental health needs on intention to use is positive and significant. This research highlights the importance of improving people's understanding of mental health, removing stigma, and developing trust in mental health service technology. It is recommended that features are developed to be easier to use, access and mental health services are improved through information and communication technology, and wider education is conducted to increase the adoption of mental health technology in the community, especially in light of the COVID-19 pandemic which has increased mental health issues globally.